2001
DOI: 10.1128/iai.69.3.1581-1586.2001
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusandSalmonella entericaSerovar Dublin Induce Tumor Necrosis Factor-Related Apoptosis-Inducing Ligand Expression by Normal Mouse and Human Osteoblasts

Abstract: Staphylococcus aureus and Salmonella enterica serovar Dublin invade osteoblasts and are causative agents of human bone disease. In the present study, we examined the ability of S. aureus and Salmonella serovar Dublin to induce the production of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) by normal osteoblasts. Normal mouse and human osteoblasts were cocultured with S. aureus or Salmonella serovar Dublin at different multiplicities of infection. Following initial incubation and examination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 38 publications
6
50
0
Order By: Relevance
“…In the presence of TRAIL, OPG loses its ability to inhibit RANKL induced osteoclastogenesis ]. Our studies showing that human osteoblasts express TRAIL confirm that of others [Alexander et al, 2001;Evdokiou et al, 2002]. And most importantly, TRAIL induces apoptosis in human osteogenic sarcoma cells, but not in normal human osteoblasts, despite their expression of the receptors for TRAIL [Evdokiou et al, 2002].…”
Section: Discussionsupporting
confidence: 87%
“…In the presence of TRAIL, OPG loses its ability to inhibit RANKL induced osteoclastogenesis ]. Our studies showing that human osteoblasts express TRAIL confirm that of others [Alexander et al, 2001;Evdokiou et al, 2002]. And most importantly, TRAIL induces apoptosis in human osteogenic sarcoma cells, but not in normal human osteoblasts, despite their expression of the receptors for TRAIL [Evdokiou et al, 2002].…”
Section: Discussionsupporting
confidence: 87%
“…Finally, infection has been proven to be a detriment to bone formation and fracture-healing in both basic-science and clinical studies and appears to favor osteoblast apoptosis and osteoclastogenesis through a complex inflammatory cascade [28][29][30][31] . However, in our series, all cultures of specimens that were obtained at the time of heterotopic ossification excision were positive.…”
Section: Etiology and Prevalence Of Traumatic And Combat-related Ampumentioning
confidence: 99%
“…Other studies have demonstrated induction of TRAIL by Theiler's murine encephalomyelitis virus (TMEV) in M1-D cells (a myelomonocytic precursor cell line) [37], reovirus infection in fibroblasts [38], HIV-1 infection in CD4 + T cells [39], and adenovirus in 239T cells [40]. The demonstration of caspase-8 involvement in S. aureus -induced apoptosis is complemented by a recent report from our laboratory that S. aureus induces expression of TRAIL by infected osteoblasts [41]. We reported that S. aureus strongly induces TRAIL expression by both normal mouse and normal human osteoblasts, while mRNAs encoding the death-domain-containing TRAIL receptors are constitutively expressed in the same cells.…”
Section: Introductionmentioning
confidence: 99%